m+33=13

Simple and best practice solution for m+33=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m+33=13 equation:


Simplifying
m + 33 = 13

Reorder the terms:
33 + m = 13

Solving
33 + m = 13

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-33' to each side of the equation.
33 + -33 + m = 13 + -33

Combine like terms: 33 + -33 = 0
0 + m = 13 + -33
m = 13 + -33

Combine like terms: 13 + -33 = -20
m = -20

Simplifying
m = -20

See similar equations:

| 24(2x-1)=6(x+3)+3 | | 2r=-8 | | =2-3x+2x^2-x^3 | | (4x-1)(x+2)=x(2x-3)-10 | | -8(2b+4)+(17b-6)=0 | | 2.5q-4.8-4.1q=-2.6q-4.7 | | 4-(2-3x)=6x-(4x+3) | | 0=-8+3z | | 2.5q-4.8q-4.1q=-2.6q-4.7 | | =2x^7+4x^6-6x^5+4x^4 | | 4(0)+y=-14 | | 4(-2)+y=-14 | | 4(-6)+y=-14 | | (y+3)(y+1)=2y(y+3) | | x^3-6*x^2+9*x-4=0 | | x^2-7x+264=0 | | x^2+8-7x+256=0 | | 36z^2-4=0 | | 1+8x=46-64x | | -0.2(x+3)=0.3(x+11) | | 9x(x)+47x+44=0 | | 2x(x)+x-2x-1=3x+6+9x | | 5x^2-60x+15=0 | | 3x^2+9x-36=0 | | a^2b-25b= | | 8x+0=72 | | 2(w+5)-8w=28 | | x^4+3x^3-28x=0 | | x^3+3x^2-28=0 | | 9(4x-6)=3(12x+8) | | 3+2x-1=9z+6-6z | | 4y+12y=128 |

Equations solver categories